Investigating the feasibility of symmetric guanidinium based plumbate perovskites in prototype solar cell devices. (10th July 2017) - Kulkarni, Sneha A.; Baikie, Tom; Muduli, Subas; Potter, Rob; Chen, Shi; Yanan, Fanan; Bishop, Peter; Lim, Swee Sien; Sum, Tze Chien; Mathews, Nripan; White, Tim J.
Abstract: In this work we have studied the feasibility of highly symmetric guanidinium (GA; CH6 N3 + ) cation in perovskite based solar cells. It is an alternative to the methyl ammonium (MA; CH3 NH3 + ) or formamidinium (FA; CH(NH2 ) 2+ ) ions commonly utilized in the perovskite solar cells, may bring additional advantages due to its triad rotational symmetry and zero dipole moment (μ). We noticed that due to steric factors, GA preferably forms two-dimensional (2D) layer, where GA2 PbI4 is favored monoclinic structure ( E g = 2.5 eV) and the obtained device efficiency is η = 0.45%. This study provides a guideline for designing guanidinium based perovskite absorbers for solar cell devices. In addition, through further compositional engineering with mixed organic cations using GA may enhance the device performance.